Polycomb recruitment attenuates retinoic acid–induced transcription of the bivalent NR2F1 gene - Laursen, Kristian B.; Mongan, Nigel P.; Zhuang, Yong; Ng, Mary M.; Benoit, Yannick D.; Gudas, Lorraine J. (Oxford Journals, 2013)
Polycomb proteins play key roles in mediating epigenetic modifications that occur during cell differentiation. The Polycomb repressive complex 2 (PRC2) mediates the tri-methylation of histone H3 lysine 27 (H3K27me3). In this study, we identify a distinguishing feature of two classes of PRC2 target genes, represented by the Nr2F1 (Coup-TF1) and the Hoxa5 gene, respectively. Both genes are transcriptionally activated by all-trans retinoic acid (RA) and display increased levels of the permissive H3K9/K14ac and tri-methylated histone H3 lysine 4 epigenetic marks in response to RA. However, while in response to RA the PRC2 and H3K27me3 marks are greatly decreased at the Hoxa5 promoter, these marks are initially increased at the Nr2F1 promoter. Functional depletion of the essential PRC2 protein Suz12 by short hairpin RNA (shRNA) technology enhanced the RA-associated transcription of Nr2F1, Nr2F2, Meis1, Sox9 and BMP2, but had no effect on the Hoxa5, Hoxa1, Cyp26a1, Cyp26b1 and RARβ2 transcript levels in wild-type embryonic stem cells. We propose that PRC2 recruitment attenuates the RA-associated transcriptional activation of a subset of genes. Such a mechanism would permit the fine-tuning of transcriptional networks during differentiation.